PENGEMBANGAN VIDEO PEMBELAJARAN BERBANTUAN GEOGEBRA TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS SISWA KELAS XI SMA NEGERI 1 SINTANG PADA MATERI PROGRAM LINEAR - Herawati Januar Ningsih; Syarifah Fadillah; Dwi Oktaviana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop Geogebra-assisted learning videos on the mathematical representation abilities of class XI students at SMA Negeri 1 Sintang on linear programming material. This research is a Research and Development (R&D) ADDIE model with five stages consisting of Analysis, Desigh (design/planning), Development (development), Implementation (implementation) and Evaluation (evaluation). The product development subjects in this research were media expert validators, namely two mathematics education subjects and one mathematics subject teacher, material experts, namely two mathematics education lecturers and one mathematics subject teacher, and the product trial subjects were class XI IPS 1 students at SMA Negeri 1 Sintang with 28 students. The data collection technique used is indirect communication techniques with research instruments in the form of validation sheets and response questionnaires, as well as measurement techniques in the form of description tests. Based on the results obtained, the conclusion in this research is that the learning videos developed are suitable for use in the learning process with the validation results from media experts and material experts obtaining validity with a percentage of 87.29% with very valid criteria; practicality was obtained from the teacher response questionnaire and student responses with a percentage of 85.89% with very practical criteria; and effectiveness measured from student test results obtained a percentage of 64.28% effective.